Internalisasi Maslahat Dalam Pendidikan Islam:Telaah Atas Pemikiran Al-Shatibi - Hanafi; Munawir; Abdul Haris; Siti Mahmudah Noorhayati (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2026)
This study examines the internalization of maslahat values in Islamic education through the framework of maqashid al-shariah formulated by Abu Ishaq al-Shatibi. Contemporary Islamic education encounters various challenges, including moral decline, materialistic tendencies, extremism, and the weakening of intellectual and spiritual traditions, which highlight the need for an educational paradigm oriented not merely toward knowledge transmission but also toward the cultivation of values and public benefit. This study aims to analyze al-Shatibi’s concept of maslahat and formulate its relevance to the reconstruction of contemporary Islamic education. Employing a qualitative approach through library research, the study analyzes primary sources, namely al-Muwafaqat fi Ushul al-Shariah and al-I’tisham, supported by secondary sources consisting of scholarly books and journal articles on maqashid al-shariah and Islamic education published between 2020 and 2025. Data were examined using descriptive, analytical, and critical approaches within the perspective of Islamic educational philosophy. The findings demonstrate that maslahat, particularly through the framework of al-kulliyyat al-khams, provides a comprehensive philosophical foundation for Islamic education. Its internalization can be realized through four interconnected dimensions: educational objectives and philosophy, an integrated curriculum based on al-kulliyyat al-khams, dialogical-reflective pedagogical methods, and educational environments that nurture the values of maslahat. The novelty of this study lies in the formulation of an integrative model of maslahat internalization based on al-Shatibi’s maqashid al-shariah, connecting philosophical, curricular, pedagogical, and socio-cultural dimensions into a coherent educational framework. This study concludes that maqashid-based Islamic education contributes to the formation of learners who possess intellectual competence, moral integrity, and social responsibility in responding to contemporary challenges.